The Influence of Balinese Culture on EFL University Students Speaking Ability - Hadisaputra, I Nyoman Pasek; Adnyani, Ni Luh Putu Sri (Universitas Pendidikan Ganesha, 2012)
The study aimed at finding out the influence of the Balinese culture to the speaking ability of Diploma 3 English Department students. The study was also to find out the efforts of the teachers in overcoming the influence of the culture. The research was conducted at Diploma 3 English Department of Undiksha and the subjects of the research were the students of semester III, year of enrolment 2006/2007. The result of the study shows that the Balinese culture influenced the speaking abilities of the students. The influences are as follows: a) being silent was a way to control situation and an effort to maintain harmony, b) saving face, c) children’s opinion was not ‘important’, d) asking personal questions were the way to do small talk, and e) smiling is a positive way to express oneself. While the teachers try to overcome the influence of the culture through conducting good classroom management, choosing interesting topics, which are also familiar to the students, giving motivation, giving assignments to improve their knowledge, and promoting good relationships between teachers and students.